2020
DOI: 10.26803/ijlter.19.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ Beliefs and Agency about Active Learning in English For Specific Purposes Classes

Abstract: This paper examines how English for Specific Purposes lecturers changed their teaching strategies that align with their beliefs about active learning at a Vietnamese university. There is a growing interest in making changes in tertiary instructional practices to involve students in active learning in response to increasing international contexts. Significant reforms of higher education in Vietnam have called for the quality of education, particularly foreign language teaching and learning. Thus, it requires te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Only two studies made an attempt to explore the concepts of teachers' resilience (Estaji & Rahimi, 2014), and quality and relevance of ESP education (Kamberi et al, 2020). The other three articles merely concern teachers' beliefs (Cao et al, 2022;Nguyen, 2020) and factors influencing such beliefs (Yang & Wyatt, 2021). Estaji and Rahimi (2014) explored ESP teachers' perceptions of resilience in relation to their professional development.…”
Section: Esp Teachers' Perceptions and Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two studies made an attempt to explore the concepts of teachers' resilience (Estaji & Rahimi, 2014), and quality and relevance of ESP education (Kamberi et al, 2020). The other three articles merely concern teachers' beliefs (Cao et al, 2022;Nguyen, 2020) and factors influencing such beliefs (Yang & Wyatt, 2021). Estaji and Rahimi (2014) explored ESP teachers' perceptions of resilience in relation to their professional development.…”
Section: Esp Teachers' Perceptions and Beliefsmentioning
confidence: 99%
“…The ESP teachers' beliefs that were elicited from teachers' perceptions on the concept of active learning (AL) in ESP classes were evidenced in Nguyen's (2020) work. This classroom-based action research aimed at exploring the five science teachers' beliefs about active learning as reported to be implemented in their ESP classes over a three-semester period.…”
Section: Esp Teachers' Perceptions and Beliefsmentioning
confidence: 99%
See 1 more Smart Citation